Community Priorities for Hospital-Based Prevention Initiatives: Results From a Deliberating Public. Issue 4 (July 2018) - Gold, Marthe R.; Realmuto, Lindsey; Scherer, Maya; Kamler, Alexandra; Weiss, Linda
Abstract : Context: Internal revenue service provisions require not-for-profit hospitals to provide "community benefit." In addition, the Affordable Care Act requires these hospitals to conduct community health needs assessments that involve appropriate stakeholders. These requirements signal government interest in creating opportunities for developing programs that are well tailored and responsive to the needs of the communities served. Gaining meaningful input from residents is a critical aspect of these processes. Objective: To implement public deliberations that explore local resident priorities for use of a hospital's community benefit resources to prevent chronic disease. Methods: Public deliberation is a method of community engagement that can provide guidance to decision makers on value-laden issues when technical solutions alone are inadequate to provide direction or set priorities. Three deliberations featuring presentations by experts and discussions among participants were convened with a cross section of residents in Brooklyn, New York. Participants were asked whether new hospital initiatives should prioritize: clinical prevention, community-based interventions, or action on broader policies affecting population health. Pre- and postsurveys, as well as qualitative methods, were used to assess knowledge and attitudes. Results: Postdeliberation, participants had significant changes in knowledge, particularly on the impact of education on health. Participants prioritized community-based and policy interventions over expanding clinical prevention capacity. Conclusions: Public deliberation offers a method to probe informed constituent views of how a hospital can best promote its community's health. Informed local residents felt that hospitals should frame health-promoting activities more broadly than is current practice. Not-for-profit hospitals gain significant tax advantages. Increased insurance rates suggest that some hospitals will experience savings in uncompensated care that can be used to promote health more broadly. Vetting priorities for the use of new resources with informed community members can be accomplished through public deliberation. These results suggest community support for nonclinical approaches to disease prevention.